Determination of jump property of some resistant genes to antibiotics in Pseudomonas aeruginosa - Khaled Ahmed; Rayan Faisel (مجلة التربية والعلم, 2008)
Abstract Forty isolates of Pseudomonas were collected from different human clinical speciemens (Urine, Stool, Sputum, Pus, Blood and Ear swab) . They were microscopically examined and their identification was confirmed by API 20E test which showed that all of them belonged to the species Pseudomonas aeruginosa .Their response to eight antibiotics used in this study was tested .There were differences in pattern of their resistance. Depending on their source of isolation six isolates were chosen to determine the transposition property of some antibiotic resistance genes carried on plasmid DNA of the chosen bacterial isolates. It was found that the isolate from ear infections contained transposon with a gene for amplicillin resistance on the plasmid DNA . These genes had the ability to jump from its location on the plasmid DNA to the chromosomal DNA of the laboratory strain E. coli JMP294 .